Design and development of a rice-husk fired fish dryer for rural fish processing industry in Malaysia. - Bardaie, Mohd. Zohadie; Wan Ismail, Wan Ishak (1984)
In Malaysia, fish contributes as much as 50 to 80 percent of the animal protein consumed. Of the total amount of fish caught, about 12 percent is processed by traditional means in the rural areas. Fish processing is a major industry, where in Peninsular Malaysia itself an estimated total of around 76,646 tonnes were processed in 1980. Fish meal and fish used for manure represented the bulk of processed fish, while 10.6% were processed into dried fish and another 12.5% into dried anchovies. Traditional practice of fish processing entails sun-drying of the fish under open air conditions. The general method of sun-drying is associated with several problems which affect the duration of drying as well as the quality of the resulting product. To overcome these problems, a dryer was developed which uses artificial heat obtained from burning of rice-husk. A heat exchanger is used as a medium of heat transfer from the burner to the clean air being circulated in the drying chamber. A 600kg (wet weight) capacity dryer was designed and fabricated for testing at Universiti Pertanian Malaysia. Results from the tests indicate the dryer is capable of drying the fish from an initial moisture content (wet basis) of 78% to a final value of 40% within a period of 12 hours.